Rates of Antimicrobial Resistance With Extended Oral Antibiotic Prophylaxis After Total Joint Arthroplasty - Christopher N. Carender, MD; Poorani Sekar, MD; Kunatum Prasidthrathsint, MD; David E. DeMik, MD, PharmD; Timothy S. Brown, MD; Nicholas A. Bedard, MD (Arthroplasty Today, 2022)
Background: There is increased interest and utilization of extended oral antibiotic prophylaxis (EOAP) following primary and revision total hip arthroplasties (THAs) and total knee arthroplasties (TKAs). The purpose of this study was to look for potential associations between EOAP and differential rates of antimicrobial resistance or epidemiology of organisms causing periprosthetic joint infection (PJI) following primary and aseptic revision THAs/TKAs. Methods: Patients who developed PJI following a primary or aseptic revision TKA/THA at a single institution from 2009 to 2020 were retrospectively identified. Patients who received at least 7 days of EOAP following the surgery were noted. Rates of antimicrobial resistance were compared between standard antibiotic prophylaxis and EOAP cohorts using the Fisher’s exact test. Results: One hundred twenty-eight cultures were obtained from 119 patients with PJI. Fourty-four cases (37%) developed PJI after EOAP. Staphylococcus aureus was the most frequently isolated organism (30% of all cultures; 78% were methicillin-sensitive). Rates of antimicrobial resistance were similar between standard antibiotic prophylaxis and EOAP cohorts in all but 2 instances: Increased resistance to erythromycin and trimethoprim-sulfamethoxazole was observed in coagulase-negative Staphylococci isolates in the EOAP cohort (89% vs 21%, P < .01; 44% vs 0%, P = .02). An increased frequency of gram-negative organisms was observed in the EOAP group (22% vs 8%, P = .03). Conclusions: Rates of antimicrobial resistance were not significantly different between EOAP and standard antibiotic prophylaxis cohorts except in coagulase-negative Staphylococci. The increased frequency of gram-negative infections was present in the EOAP cohort. Larger, multicenter studies are needed to better understand the impact of EOAP on antimicrobial resistance and PJI epidemiology. Level of Evidence: Level III; retrospective cohort study.